2013
DOI: 10.1037/a0029767
|View full text |Cite
|
Sign up to set email alerts
|

Integrating brain and behavior: Evaluating adolescents’ response to a cannabis intervention.

Abstract: Client language (change talk [CT] and counterchange talk [CCT]) is gaining increasing support as an active ingredient of psychosocial interventions. Preliminary work with adults suggests that there may be a neural basis for this. With a diverse sample of adolescent cannabis users, we evaluated the influence of CT and CCT on blood oxygen level dependent (BOLD) response during an fMRI cannabis cue-exposure paradigm. We also investigated how BOLD activation related to treatment outcomes. Adolescent cannabis users… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(82 citation statements)
references
References 91 publications
(148 reference statements)
2
80
0
Order By: Relevance
“…Fronto-temporal regions have been broadly linked to working memory and attention (8890), functions that are essential to academic and vocational performance, and also shown to be suppressed among adults who are heavy users of cannabis (91,92). In addition, psychosocial interventions for a range of problem health behaviors have been shown to modulate activity in mesial temporal lobe (24,93,94), which may suggest a role for this region in treatment response. Given the effects of cannabis use in early adolescence on cognitive function (4,5), it remains possible that the relationship between cannabis dependence and activity in the fronto-temporal network observed in the present study reflects the near-term sequelae of cannabis use.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fronto-temporal regions have been broadly linked to working memory and attention (8890), functions that are essential to academic and vocational performance, and also shown to be suppressed among adults who are heavy users of cannabis (91,92). In addition, psychosocial interventions for a range of problem health behaviors have been shown to modulate activity in mesial temporal lobe (24,93,94), which may suggest a role for this region in treatment response. Given the effects of cannabis use in early adolescence on cognitive function (4,5), it remains possible that the relationship between cannabis dependence and activity in the fronto-temporal network observed in the present study reflects the near-term sequelae of cannabis use.…”
Section: Resultsmentioning
confidence: 99%
“…This variability in treatment outcomes may be due, in part, to our limited understanding of how psychotherapy works (21), especially for adolescents (22,23). Evaluations of basic biological factors hold great promise for deconstructing adolescents' patterns of intervention response (2426). The measurement of these factors, such as resting brain activity, may ultimately yield better-targeted interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding which regions of cognitive control and reward-related circuitry are disrupted prior to initiation of alcohol use, and which are disrupted by alcohol use itself, potentially further perpetuating intake, is crucial for identifying targets for future prevention and intervention strategies. In fact, recent studies have begun to use such findings, alongside behavioral intervention strategies, to elicit functional changes in the brain of substance users (Feldstein Ewing et al, 2013), highlighting the importance of these neuroimaging findings for future translational research.…”
Section: Discussionmentioning
confidence: 99%
“…In the most integrated translational project to date, Feldstein Ewing and colleagues (2013) utilized fMRI to measure the impacts of psychological treatment (change talk versus counterchange talk) on brain activation to cannabis cues following treatment in teenage cannabis-users. They found that change talk increased BOLD activation in areas that underlie introspection (posterior cingulate, precuneaus) during exposure to cannabis cues, and this increase in activation was associated with superior one-month treatment outcomes (frequency of cannabis use, MJ-related problems, CUD symptoms).…”
Section: Future Research Directionsmentioning
confidence: 99%